1974
DOI: 10.1055/s-0028-1095713
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone and Calcitonin: Influences upon Lipolysis of Human Adipose Tissue

Abstract: Calcium ions are of irnportance for the function of every cell in the organism, and this applies also for the fat eells. In incubated slices of rabbit adipose tissue, ACTH-or epinephrine-stirnulated Iipolysis was accompanied by an increase in.tissue calcium (A/cgün and Rudman 1969). Werner and Löw (1973, 1974) investigated the effects of the hormones of calcium homeostasis, parathyroid hormone and calcitonin, upon lipolysis of incubated rat adipose tissue pieces and demonstrated that parathyroid hormone induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This ,8-blocking agent had no effect on the 1- (5)(6)(7)(8)(9)(10). It has been shown that parathyroid hormone can promote lipolysis in human adipocytes (14,15 (14,15). These hormone concentrations are unplhysiologically high.…”
Section: Introductionmentioning
confidence: 91%
“…This ,8-blocking agent had no effect on the 1- (5)(6)(7)(8)(9)(10). It has been shown that parathyroid hormone can promote lipolysis in human adipocytes (14,15 (14,15). These hormone concentrations are unplhysiologically high.…”
Section: Introductionmentioning
confidence: 91%
“…PTH promotes mobilization of calcium from bone by increasing bone resorption and the kidney's production of 1,25-dihydroxyvitamin D in conditions of serum hypocalcemia (de Paula and Rosen 2010). Both singledose and intermittent PTH treatments stimulate lipolysis of white adipose tissue and the production of glycerol in a dose-dependent manner, also linking PTH and adiposity (Gozariu et al 1974;Sinha et al 1976). Intermittent PTH treatment inhibits the differentiation of adipocytes (Rickard et al 2006;Kulkarni et al 2007).…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…It has been shown that parathyroid hormone (PTH) can promote lipolysis in h u m a n lipocytes [2,11]. We were recently able to demonstrate that the adenylate cyclase system of human fat cell ghosts reacts to at least t w o different classes of hormones:…”
Section: Lipolysismentioning
confidence: 99%